2016
DOI: 10.1002/cbdv.201600118
|View full text |Cite
|
Sign up to set email alerts
|

Hexane Extract of Echinops spinosissimus Turra subsp. spinosus from Tunisia: A Potential Source of Acetylated Sterols – Investigation of its Biological Activities

Abstract: The hexane extract of Echinops spinosissimus Turra subsp. spinosus flower heads was analyzed for its fatty acid and sterol composition. Its physicochemical characteristics were also studied. The saponification, iodine and peroxide values were determined as 255 mg KOH/g, 42.57 g I /100 g and 110 m equiv. O /kg of oil, respectively. The oleic (C18:1; 61.14%), palmitic (C16:0; 21.36%) and linoleic (C18:2; 10.45%) acids were the dominant fatty acids. This extract was also found to contain high levels of β-sitoster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Phytochemical investigations of E. spinosus from North Africa in Morocco, Algeria, Tunisia, and Egypt led to the isolation and identification of 42 metabolites belonging to the phytochemical classes of quinoline alkaloids (S 1 -S 2 ) [1], sesquiterpenoids (S 3 ) [22], flavonoids (S 4 -S 26 ) [12,23], and sterols (S 27 -S 39 ) [24]. The names of the isolated compounds and their sources are provided in Table 1 and the chemical structures are depicted in Table 2.…”
Section: Phytochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Phytochemical investigations of E. spinosus from North Africa in Morocco, Algeria, Tunisia, and Egypt led to the isolation and identification of 42 metabolites belonging to the phytochemical classes of quinoline alkaloids (S 1 -S 2 ) [1], sesquiterpenoids (S 3 ) [22], flavonoids (S 4 -S 26 ) [12,23], and sterols (S 27 -S 39 ) [24]. The names of the isolated compounds and their sources are provided in Table 1 and the chemical structures are depicted in Table 2.…”
Section: Phytochemistrymentioning
confidence: 99%
“…In 2009, the isolation of two sesquiterpenoids with a novel carbon framework was reported and named echinopine A and echinopine B [22]. In 2016, Bouattour et al [24] identified 13 sterols in E. spinosus from Tunisia. The two most abundant compounds were ß-sitosterol (44.97%) followed by stigmasterol (34.95%) [24].…”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the genus E. s. spinosus, the ethanolic extract has efficient action on muscular fibers and exhibited a very good anti-inflammatory activity [16]. It was known for its therapeutic effect on health and its extensive anecdotal history in traditional medicines [17]. The Gas chromatography and Mass spectrometry analysis demonstrated that the plant is a potential source of terpenoid compounds and acetylated sterols [17].…”
Section: Introductionmentioning
confidence: 99%
“…It was known for its therapeutic effect on health and its extensive anecdotal history in traditional medicines [17]. The Gas chromatography and Mass spectrometry analysis demonstrated that the plant is a potential source of terpenoid compounds and acetylated sterols [17].…”
Section: Introductionmentioning
confidence: 99%